Facing complexity, crisis, and risk: Opportunities and challenges in international human resource management. (6th February 2019) - Farndale, Elaine; Horak, Sven; Phillips, Jean; Beamond, Maria
Abstract : International human resource management (IHRM) as a field of practice involves heightened levels of complexity compared to domestic HRM based on the multitude of contexts in which multinational firms operate. As complexity increases, so do levels of risk and the chance the firm must deal with crisis situations. Based on articles presented at the 3rd Global Conference on IHRM, this special issue focuses on how IHRM can contribute to organization success when faced with extreme operating conditions. This editorial provides a backdrop to the articles by describing the challenging economic, political, and social environments impacting organizations, exploring conditions from the recent past and current day such as the global financial crisis, trends toward political nationalism, aging populations, and growing immigrant workforces. The focus lies on exploring how HRM can respond to such challenging external contexts to continue to contribute added value to the firm.